2018
DOI: 10.1002/biof.1427
|View full text |Cite
|
Sign up to set email alerts
|

Lyso‐DGTS lipid isolated from microalgae enhances PON1 activities in vitro and in vivo, increases PON1 penetration into macrophages and decreases cellular lipid accumulation

Abstract: High-density lipoprotein (HDL) plays an important role in preventing atherosclerosis. The antioxidant effect of HDL is mostly associated with paraoxonase 1 (PON1) activity. Increasing PON1 activity using nutrients might improve HDL function and quality and thus, decrease atherosclerotic risk. We previously isolated and identified a novel active compound, lyso-DGTS (C20:5,0) from Nannochloropsis sp. ethanol extract. In the present study, its effect on PON1 activities was examined and the mechanism by which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…Determines interactions between flavonoids and proteins, quantitative analysis of binding affinities and thermodynamic parameters [21,41,42] docking calculations…”
Section: Methods For Characterizing Flavonoid-protein Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Determines interactions between flavonoids and proteins, quantitative analysis of binding affinities and thermodynamic parameters [21,41,42] docking calculations…”
Section: Methods For Characterizing Flavonoid-protein Interactionsmentioning
confidence: 99%
“…Tryptophan (Trp)-fluorescence quenching assay is another sensitive, selective, and widely used method for determining interactions between flavonoids and proteins [21,41,42]. The excitation of proteins at 280-290 nm induces the emission of fluorescence in the range of 340-350 nm due to the presence of Trp.…”
Section: Methods For Characterizing Flavonoid-protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…PON1 hydrolyses a wide range of substrates, such as esters, thioesters, phosphotriesters, lactones and thiolactones, as well as 5-thioalkyl butyrolactones [34]. The main physiological role of PON1 appears to be the hydrolysis of oxidized lipids in macrophages that yields lyso-glycerophosphatidyl lipids in cell membranes [35] and provides protection against protein N-homocysteinylation [36]. The highest activities observed in vitro are against the synthetic substrates PA for esterase and dihydrocumarine for lactonase activity [10,11] that have no A comparison of the size of the carbamates and their positioning in the active site revealed that the more voluminous carbamates, bambuterol (360 Å 3 ) and Ro 02-0683 (318 Å 3 ), form hydrogen bonds with Asp269 that are involved in the ligation of catalytic Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Other MGDG, DGDG, and SQDG-rich extracts attenuated croton–oil-induced oedema in a mice model [ 24 ]. An isolated betaine lipid, MGTS(20:5), was responsible for the inhibition of LDL oxidation through the increased expression of paraoxonase 1 (PON1) in J-774A macrophages [ 78 , 79 ].…”
Section: The Anti-inflammatory Potential Of Microalgal Lipid Extractsmentioning
confidence: 99%